Memori dan Trauma dalam Hubungan Internasional: Pengaruh Isu â€œComfort Womenâ€ terhadap Kerjasama Keamanan Jepang dan Korea Selatan - Adityani, Fiandara Dwi; Susiatiningsih, Hermini; Paramasatya, Satwika (Journal of International Relations, 2018)
Japan and South Korea have a complicated relations ever since Japanâ€™s occupation in Korean Peninsula in 1910. During Japanâ€™s occupation, Japanese military abducted thousands of Korean women to work in a military brothel and serve as a sex slaves for Japanese forces, or known as â€œcomfort womenâ€. Trauma left by Japanese colonial rule created mutual animosities which hamper bilateral relations between both countries. In 2012, South Korea back off from the first military cooperation pact with Japan, due to overflow public resentment in South Korea toward Japan. The objective of this research is to understand how â€œcomfort womenâ€ issue impacted bilateral security cooperation between Japan and South Korea. This research used qualitative methods alongside with the concept of memory, war, and world politics to explain how memory and trauma shape South Koreanâ€™s perception toward Japan, as well as the concept of Public Opinion, Domestic Structure, and Foreign Policy in Liberal Democracies to explain the impact of public opinion toward South Koreaâ€™s foreign policy. The result of this research indicated that history of â€œcomfort womenâ€ created collective memory in South Korea, which hampers its bilateral security cooperation with Japan. The bilateral security cooperation between Japan and South Korea established only after two nations reach consensus in â€œcomfort womenâ€ issue.